2013
DOI: 10.1108/ejm-07-2011-0371
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of brand-oriented companies

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 64 publications
(117 reference statements)
3
65
0
1
Order By: Relevance
“…Thus, it can be assumed that positive attitude leads to high consumer-based brand equity. Huang and Tsai (2013) suggested that brand awareness is one of the factors that companies with a brand orientation enjoy. Brand awareness is one of the most important components in creating brand equity (Seno and Lukas 2007); hence, it is reasonable to propose that a high level of consumer awareness toward a brand may lead to high consumer-based brand equity.…”
Section: The Effects Of Brand Image and Respective Drivers On Brand Ementioning
confidence: 98%
“…Thus, it can be assumed that positive attitude leads to high consumer-based brand equity. Huang and Tsai (2013) suggested that brand awareness is one of the factors that companies with a brand orientation enjoy. Brand awareness is one of the most important components in creating brand equity (Seno and Lukas 2007); hence, it is reasonable to propose that a high level of consumer awareness toward a brand may lead to high consumer-based brand equity.…”
Section: The Effects Of Brand Image and Respective Drivers On Brand Ementioning
confidence: 98%
“…Given the significant amount of knowledge they have about the brand, its operations and level of performance (e.g., Huang and Tsai, 2013), senior-level personnel responsible for overseeing the day-to-day management of the brands were targeted as key informants, to whom self-administered surveys were dispatched through the assistance provided by a professional market research firm. Informants were instructed to focus specifically on the brand for which they were managerially responsible.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Finally, brand orientation also requires the shared brand vision of the organizational members (Wong, & Merrilees 2008, Wong, & Merrilees, 2007 and the putting of brand main values and promises into daily practice (Baumgarth, 2010). Researches on internal branding have indicated the importance of establishing a brand culture (Huang, and Tsai 2013). As a result, the establishment of brand orientation is influenced by organizational culture (Hirvonen, & Laukkanen 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Businesses are planning brand orientation marketing activities to ensure sustainable competitiveness. Some of the academic studies in this area are performed by Hu et al (2012); Huang and Tsai (2013) ;Wong, ve Merrilees (2007) ;Wong, ve Merrilees (2008); Hirvonen, & Laukkanen (2014). Moreover, in order to fulfill the main values of the brand and create unique customer values, brand orientation also necessitates the combination of the knowhow and personnel skills at different internal departments in a company (Hirvonen, & Laukkanen 2014, Hu et al 2012).…”
Section: Literature Reviewmentioning
confidence: 99%